Evaluating The Efficiency Of Indonesia’s Secondary School Education - Akbar, Riznaldi (Jurnal Pendidikan Indonesia, 2018)
This study employs a Data Envelopment Analysis (DEA) to investigate secondary school efficiency and Stochastic Frontier Analysis (SFA) to examine determinants that affect average secondary school student score in Indonesia. Using the DEA, this study measures the efficiency of the region with regards to the average student score using various input indicators including teacher-to-student ratio, number of teachers holding the first-degree qualification, average secondary school expense, average duration to school and average distance to school, while output variable is the average student score for 33 regions in Indonesia. The findings suggest the average technical efficiency of secondary school in the region is 89 percent with the most efficient regions are Sumatera Utara, Kepulauan Bangka Belitung, DKI Jakarta, Jawa Timur, Bali, Sulawesi Barat, Maluku, Maluku Utara and Papua Barat. With the SFA, this study identifies factors that significantly affect the average student score in the region. The results suggest that the higher ratio of teacher-to-student and higher numbers of the teacher with the first-degree qualification significantly affect the average student score in the region. However, there is no evidence that average secondary school expense and school proximity (average duration and distance to school) significantly affect secondary school efficiency.